THE ROLE OF INVESTMENTS IN THE ECONOMY OF UZBEKISTAN - Rustamova Dilafruz (Ecomind Press, 2025)
This scientific article gives ideas and reflections on investment, its role and significance in the economy of Uzbekistan.
Keywords: Economy, finance, investment, capital, foreign investment, project, efficiency.